Plant extracts against rice leaf blight from histopathological aspect - Toàn, Lê Thanh; Bình, Văng Viết (Hue University Journal of Science: Natural Science, 2021)
Leaf blight is one of the most severe bacterial diseases in most rice-cultivating countries all over the world. Therefore, this research was carried out to seek effective plant extracts for managing this disease. The extracts of garlic, tamanu, and periwinkle were utilized as pure and combined with the zinc acetate solution 1 mM. Under in vitro conditions, the pure extract of periwinkle and its combination with zinc acetate induces the inhibition efficiency against Xanthomonas oryzae pv. oryzae of approximately 24.32 and 100%, respectively. In net houses, the seed-soaked and foliar sprayed treatments at 15, 30, and 45 days after growing cause rice plants to produce bactericide polyphenol compounds, and the effect lasts until 96 hours after pathogen inoculation. The disease reduction of treated rice leaves lasts to the 14th day after pathogen inoculation. At this moment, the pathogen density in treated leaves is lower than that of the control.